Phronetic perspective in policy analysis: An investigation on national climate change policy in Malaysia / Ezwan Arman Noor Kamar - Ezwan Arman , Noor Kamar (2015)
Climate change has become a major issue around the world. In the recent period, the impact of climate change has grown enormously, and almost impossible for a country to deal with its effects alone. Climate change has major implications, which includes not only scientific, but also political, economic, socio-cultural, psychological, and ethical, which should be understood by policy makers and society in order to respond effectively to this issue. Nevertheless, policy makers wield a great deal of influence in shaping the meaning of climate change and in developing and executing adaptation and mitigation plans and strategies for countries and their inhabitants. Due to the omnipresent influence of positivism in social research, the field of policy studies has been dominated by empiricism to the study of politics and rule in society that indirectly obscures the diversity, complexity and diffusive dimensions of governance. Although policy process has advanced through the application of Habermasian communicative action in recent decades; this focus on public participation, discourse, and consensus leaves little space for investigations of values and power relations underlying attempts to plan for a sustainable future. In the face of climate change, Malaysia has implemented climate change policy in line with the international political scene. This thesis explores phronesis as an alternative theory of practice for policy makers who share the idea of climate change. In it, climate change policy planning requires an amended set of theoretical and practical tools; and explore the idea that practical wisdom are among the skills that policy makers required; who are interested in climate change will need to cultivate, supported by wise and creative planning theory. Phronesis develops principles derived from or relating to experience as opposed to other methods of acquiring knowledge, and setting them against empirical evidence, to be effective. Phronesis gives balance towards the empirical approaches, rationale for action and a focus for the development of alternative methods and approaches. This thesis adopts ‘phronetic planning research’ introduced by Flyvbjerg to investigate the National Climate Change Policy in Malaysia. Two central objectives are pursued: 1) to provide critical analysis of climate change policy in Malaysia through a phronetic research approach; and 2) to analyze the efficacy of climate change policy in Malaysia from a multi-stakeholder perspectives. By analyzing the phenomenon of phronesis in policy analysis, this study seeks to contribute in field of Science and Technology Studies. It also presents a narrative of phronetic research on policy analysis that will enrich literature in policy studies as well as in environmental studies. This study relies on data and information gathered through fieldwork in several states in Malaysia. Two methods were used: (a) in-depth interviews with policymakers, NGOs, environmental activists, academicians, and private sectors; and (b) archival studies method to trace climate change data in policy texts, technical documents, and mass media reports. Accordingly, as the basis for a research method, phronesis is best expressed through narratives of practice that interconnect on how strategies, goals, constraints, affordances and resources unfold in the enactment of climate change policy in Malaysia.